Quality Indicators to Subsidize Soil Conservation Under Pasture in Brazil - Costa, Adriana Monteiro; Fernandes, Luís Filipe Sanches; Pacheco, Fernando António Leal; Valera, Carlos Alberto (Land degradation & development, 2025)
ABSTRACT The management of cultivated areas has been the subject of scientific and political debate because of its adverse effects on soil health and associated ecosystem services. A route to bring degraded cultivated areas back to sustainable production systems includes implementing adequate management practices and, in parallel, monitor their results. Monitoring must be based on the periodical evaluation of soil quality indicators. The selection of indicators is, however, a challenge, because suited indicators must be simultaneously rigorous and practical to assess in the field. Thus, the aim and novelty of this study was to summarize soil quality indicators dispersed in the scientific literature, and propose an assortment of those capable of being used in soil conservation policies and management plans considering the aforementioned requisites. To our best knowledge, this kind of exhaustive summary with focus on policy and management is lacking. To accomplish the proposed goal, a systematic literature review was carried out using the Scopus database. The selection of articles followed the guidelines of PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses). The results revealed that, indicators such as organic carbon, soil structure assessments, and erosion monitoring are practical for public policy due to their cost‐effectiveness and ease of field application. Besides, they are suited for evaluation through technologies like remote sensing and portable sensors. Additional results from the review exposed that the current understanding of soil quality across the various Brazilian biomes is limited by geographic and methodological biases in the existing studies, and that it is essential to invest in infrastructure, methodological standardization and stakeholder training to fill in those gaps. Finally, the present review emphasized the need to conduct future studies based on interdisciplinary collaboration, as measure to reach a common language a view over how to assess and use indicators as proxies of soil quality and health, and ultimately to promote sustainable land use and soil conservation in Brazil.